2023
DOI: 10.1002/cbdv.202300744
|View full text |Cite
|
Sign up to set email alerts
|

Parazoanthus axinellae Extract Incorporated Hybrid Nanostructure and Its Potential Antimicrobial Activity**

Abstract: This study, it was aimed to examine the change in the antimicrobial effect of sea anemone Parazoanthus axinellae extract by forming its nanoflowers. A scanning electron microscope (SEM) and Energy dispersive X‐ray spectroscopy (EDX) were expended to observe the morphologies of the Cu NFs that had been produced. Fourier transform infrared spectroscopy (FT‐IR) and X‐ray diffraction (XRD) techniques were expended to analyze the managing assemblies in Parazoanthus axinellae extract, which perform an effective part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
0
0
0
Order By: Relevance
“…Thus, finding antibacterial capable of combating GBS represents a challenge due to its high incidence among parturients and their neonates worldwide and the development of its antibiotic resistance [80]. Moreover, previous studies showed an antimicrobial activity of P. axinellae extract incorporated nanostructures against the Gram-positive bacterial strain Staphylococcus aureus and the Gram-negative bacterial strain Aeromonas hydrophila, Aeromonas sobria, Escherichia coli, and Salmonella enterica as reported by Konuklugil et al [81]. In this scenario, further investigations will be needed in order to isolate the potential molecules responsible for the antibacterial activities and our results pave the way for the identification of these interesting bio-compounds requiring further integrated analytical approaches, such as metabolomic, HPLC, GC-MS, and LC-MS methods.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, finding antibacterial capable of combating GBS represents a challenge due to its high incidence among parturients and their neonates worldwide and the development of its antibiotic resistance [80]. Moreover, previous studies showed an antimicrobial activity of P. axinellae extract incorporated nanostructures against the Gram-positive bacterial strain Staphylococcus aureus and the Gram-negative bacterial strain Aeromonas hydrophila, Aeromonas sobria, Escherichia coli, and Salmonella enterica as reported by Konuklugil et al [81]. In this scenario, further investigations will be needed in order to isolate the potential molecules responsible for the antibacterial activities and our results pave the way for the identification of these interesting bio-compounds requiring further integrated analytical approaches, such as metabolomic, HPLC, GC-MS, and LC-MS methods.…”
Section: Discussionmentioning
confidence: 99%